2018
DOI: 10.1155/2018/9460456
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI and Computational Modelling in the Assessment of Human Articular Cartilage Properties: A Comprehensive Approach

Abstract: Quantitative magnetic resonance imaging (qMRI) is a promising approach to detect early cartilage degeneration. However, there is no consensus on which cartilage component contributes to the tissue's qMRI signal properties. T1, T1ρ, and T2⁎ maps of cartilage samples (n = 8) were generated on a clinical 3.0-T MRI system. All samples underwent histological assessment to ensure structural integrity. For cross-referencing, a discretized numerical model capturing distinct compositional and structural tissue properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 58 publications
1
37
1
Order By: Relevance
“…Moreover, condensation and deformation of the ECM induce interstitial water redistribution within and out of the tissue and increases in proteoglycan and collagen concentration 27 . As T1r is only weakly (if at all) associated with the individual tissue constituents 11,12,28 , it is the slow spinmotions and their interactions with the fluid and solid phases 29 that are the likely imaging correlates of the loading-induced increases in T1r. However, the exact sensitivity and specificity of T1r remains to be clarified with some studies suggesting specificity for proteoglycans 28,30 , while others refuted any such specificity 11,12 .…”
Section: Tissue Functionality In Intact Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, condensation and deformation of the ECM induce interstitial water redistribution within and out of the tissue and increases in proteoglycan and collagen concentration 27 . As T1r is only weakly (if at all) associated with the individual tissue constituents 11,12,28 , it is the slow spinmotions and their interactions with the fluid and solid phases 29 that are the likely imaging correlates of the loading-induced increases in T1r. However, the exact sensitivity and specificity of T1r remains to be clarified with some studies suggesting specificity for proteoglycans 28,30 , while others refuted any such specificity 11,12 .…”
Section: Tissue Functionality In Intact Tissuementioning
confidence: 99%
“…As T1r is only weakly (if at all) associated with the individual tissue constituents 11,12,28 , it is the slow spinmotions and their interactions with the fluid and solid phases 29 that are the likely imaging correlates of the loading-induced increases in T1r. However, the exact sensitivity and specificity of T1r remains to be clarified with some studies suggesting specificity for proteoglycans 28,30 , while others refuted any such specificity 11,12 . Nonetheless, it is commonly agreed that T1r is a surrogate parameter for the tissue's macromolecular constitution and functional properties 5,7,8,13,14 .…”
Section: Tissue Functionality In Intact Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Under loading, the deeper radial collagen fibers display fiber crimping 31,39 , which increases the percentage of fibers oriented at magic angle and reduces residual dipolar interaction, thereby increasing T1ρ (as well as T2) values. Moreover, recent literature reports have disproven the previously assumed proteoglycan specificity of T1ρ and qualified this association as weak 35,40,41 so that loading-induced compositional changes may only be secondary. Consequently, T1ρ nowadays is considered a marker of the tissue's macromolecular constitution with sensitivity to its solid and fluid constituents.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, T1ρ nowadays is considered a marker of the tissue's macromolecular constitution with sensitivity to its solid and fluid constituents. Recently, positive correlations of T1ρ with fluid fraction and collagen fiber orientation, and negative correlations with collagen and proteoglycan content were reported 35 . Moreover, earlier studies by us and others have reported this parameter's exquisite mechanosensitivity and loading-induced changes in T1ρ in a range of pre-clinical and clinical contexts 17,21,22,42,43 .…”
Section: Discussionmentioning
confidence: 99%